1997
DOI: 10.1200/jco.1997.15.2.604
|View full text |Cite
|
Sign up to set email alerts
|

Vinorelbine as neoadjuvant chemotherapy in advanced cervical carcinoma.

Abstract: VNB is an active drug against ACC with moderate toxicity. Its activity is among the highest reported for single agents. Further evaluation in association with other agents is clearly justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 16 publications
0
28
0
1
Order By: Relevance
“…However, several randomized trials of NACT before radiation have not demonstrated a survival benefit compared with radiation therapy alone. [15][16][17][18][19][20][21][22][23] In many parts of the world, NACT before surgery is an accepted treatment for locally advanced stages of cervical cancer. An advantage of chemotherapy in this setting is the potential significant reduction in tumor burden, which facilitates surgical excision in previously inoperable tumors.…”
Section: Neoadjuvant Chemotherapy Before Radiotherapymentioning
confidence: 99%
“…However, several randomized trials of NACT before radiation have not demonstrated a survival benefit compared with radiation therapy alone. [15][16][17][18][19][20][21][22][23] In many parts of the world, NACT before surgery is an accepted treatment for locally advanced stages of cervical cancer. An advantage of chemotherapy in this setting is the potential significant reduction in tumor burden, which facilitates surgical excision in previously inoperable tumors.…”
Section: Neoadjuvant Chemotherapy Before Radiotherapymentioning
confidence: 99%
“…In chemotherapynaïve patients with advanced or recurrent squamous cervical carcinoma, treatment with paclitaxel 170-250 mg/m 2 results in a response rate of 17%-23% [18,19]. Treatment with weekly vinorelbine 30 mg/m 2 in previously untreated patients with recurrent cervical cancer resulted in an overall response rate (ORR) of 45% [23]. Therefore, the 38 Topotecan in Cervical and Uterine Carcinoma activity of these agents and others should be investigated as radiosensitizers in the first-line setting.…”
Section: Current First-line Treatment Strategiesmentioning
confidence: 99%
“…Further, because persistent and recurrent cervical cancer are not usually responsive to reirradiation, first-line treatment offers the best possibility for a cure. Therefore, several new cytotoxic agents have been recently investigated in the first-line treatment of cervical cancer patients (Table 1) [18][19][20][21][22][23]. In chemotherapynaïve patients with advanced or recurrent squamous cervical carcinoma, treatment with paclitaxel 170-250 mg/m 2 results in a response rate of 17%-23% [18,19].…”
Section: Current First-line Treatment Strategiesmentioning
confidence: 99%
“…However, several randomized trials of such treatment revealed no survival advantage compared with radiation therapy alone (Chiara et al, 1994;Herod et al, 2000;Lacava et al, 1997;Leborgne et al, 1997;Sundfor et al, 1996;Souhami et al, 1991;Symonds, 2000;Tattersall et al, 1992;Tattersall et al, 1995). Furthermore, the Neoadjuvant Chemotherapy for Locally Advanced Cervical Cancer MetaAnalysis Collaboration Group presented a systematic review and meta-analysis of individual patient data (IPD) from eighteen trials with 2,074 patients.…”
Section: Neoadjuvant Chemotherapy Before Radiation Therapymentioning
confidence: 99%